Work and Training Conditions of German Residents and Young Radiologists in Interventional Radiology – A Nationwide Survey - Sieren, Malte; Katoh, Marcus; Mahnken, Andreas H.; Reimer, Peter; Westphalen, Kerstin; Hoffmann, Ralf-Thorsten; Paprottka, Philipp; Rohde, Stefan; Wacker, Frank K.; Minko, Peter; Molwitz, Isabel; Oechtering, Thekla Helene; Afat, Saif; Bucher, Andreas Michael; Gerwing, Mirjam; Storz, Corinna; Ziegler, Henrike-Renate; Barkhausen, Jörg; Frisch, Anne (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
With the increasing need for minimally invasive procedures based on lower complication rates, higher patient acceptance, and technical developments, there is a growing focus on the sound interventional training of young radiologists. This survey aimed to analyze the current situation in interventional radiology (IR) training in Germany to detect shortcomings and identify areas for improvement.From November 1–30, 2020, an online questionnaire was distributed to representative radiological associations and societies with the request to forward it to radiology residents and radiologists < 40 years. The 44 questions covered six distinct areas from personal working conditions to the characterization of the IR department, training conditions, role of women in IR, and attendance at congresses/external training.A total of 330 participants completed the questionnaire. 77 % of participants expressed a high interest in IR, and 47 % could even imagine subspecializing in interventional radiology. Most institutions provided the necessary learning conditions and infrastructure. The rate of overall satisfaction with IR training conditions was 45 % (vs. a dissatisfaction rate of 39 %). However, females showed a lower satisfaction rate with their training environment than male participants (28 % vs. 51 %; P = 0.06). Positive correlations with work satisfaction were found for the presence and duration of the IR rotation, the number of partly independently/mentored performed interventions, and structured feedback. Moreover, the need for a structured training curriculum was expressed by 67 % of participants.Radiological residents and young radiologists expressed a high interest in interventional radiology, and they rate the infrastructure of German hospitals regarding IR as sufficient. However, they expressed the need for consistent IR rotations and better-structured resident and postgraduate education (curricula & interviews).Interest in interventional radiology among radiological residents and young radiologists in Germany is high, but satisfaction with interventional radiology training leaves room for improvement. The most frequently mentioned aspects that can improve IR training wereCitation Format
Keywords: interventional procedures; education; structured curriculum; neurointerventions